The Trend of Non-Communicable Diseases in Kenya from 2010 - 2020 - Gerry Mtike (Adventist University of Africa, 2022)
Background: Non-communicable diseases (NCDs) are increasingly affecting developing nations such as Kenya. These diseases include cardiovascular diseases (CVDs), chronic respiratory diseases (CRDs), cancers, diabetes, and mental illnesses. The nation has increasingly been affected by NCDs as opposed to the historic prevalence of communicable diseases. This poses a challenge as they can result in a consistent state of disability in affected individuals. A lack of awareness may be impacting the prevalence of NCDs in Kenya and their causes, including modifiable and non-modifiable factors. Method: This article utilized a systematic review to critically describe the prevalent NCDs in Kenya as well as provide five practical steps that can be taken to encourage a healthier population that is aware and actively fighting against NCDs. Results: Lifestyle-related diseases such as CVDs, COPD, cancers, diabetes, and mental illnesses are ever-increasing in Kenya. Their prevalence has increased over the last 10 years in the nation and has been silently wreaking havoc among a population that is not well educated. Conclusion: With enough dedicated focus on understanding and treating lifestyle-related diseases, there can be positive progress made to reverse the increasing trend of lifestyle-related diseases in the country.